(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
An experiment for the agricultural season2017-2018 was carried out with Rosa spin lath hose in Plant production Dept. Technical College Al-Mussaib in order to study the effect of the amino acid the Drin and Humic acid in some vegetative and floral qualities are Included(Plant height, number of branches plant-1, leaf area, number of leaves per plant, number of flowers, leaf content of chlorophyll , nitrogen, phosphorus and potassium)The Experiment included two factors, the first factor, foliar spray of amino acid Drin of three concentrations (0, 4, 8 ml.L-1), 2nd factor was soil application of Humic acid concentrations (0, 4 ml.L-1) and tree seedlings for each treatment with three replicates . The cutting was planted at the beginning of December In polyethylene bags after filling it with the loam soil the bags were irrigated and followed up during the research period, seedlings were sprayed with the Drin in three dates (1, 15 and 30 April 2018). A Factorial experience has been applied with a Completely Randomized Design (CRD) was applied and all treatments were randomized, the statistical analysis of the data was performed using the Genstat 2010 and the mean of the treatments was measured with the least significant difference at the 5%. Results showed that the Drin with a concentration of 8 ml. L-1 gave the significant rate in the qualities (Plant height, number of branches plant-1, leaf area, number of leaves per plant, number of flowers, leaf content of chlorophyll, nitrogen, phosphorus, and potassium). On the other hand, Humic acid with 4 ml. L -1 was significantly in studied traits. Interaction between the treatment of Drin at 8 ml. L-1 with humic acid 4 ml. L-1 give the highest rate in the studied traits.